Identification of Active Compounds of Eucheuma spinosum as Antidiabetic and Antioxidant Candidates: Metabolomic and In Silico Approaches - Arafah Nurfadillah; Ade Irma; Julianti Bunga (The Indonesian Institute of Science and Technology Research, 2025)
Diabetes mellitus (DM) is a non-communicable disease with an increasing global prevalence, and the long-term use of synthetic antidiabetic drugs is often associated with adverse side effects. Therefore, the exploration of natural antidiabetic agents with high efficacy and minimal toxicity is urgently needed. Red algae Eucheuma spinosum has been reported to contain bioactive metabolites with various pharmacological activities; however, its antidiabetic and antioxidant potential remains insufficiently explored. This study aimed to evaluate the antidiabetic and antioxidant activities of E. spinosum through integrated in vitro and in silico approaches. Metabolite profiling using LC-HRMS identified 2,373 compounds in the alga extract. Antioxidant assays revealed strong activity with an IC₅₀ value of 97.72 ppm. In vitro antidiabetic assays demonstrated inhibitory activity against α-amylase and α-glucosidase enzymes. Eighteen compounds with the highest abundance were selected for molecular docking and molecular dynamics simulations against 1B2Y, 5NN8, and 1CB4 target proteins. The results indicated that Undecyl 3,4,5-trihydroxybenzoate and nobiletin exhibited strong binding affinity and stable interactions with all three receptors. These findings suggest that E. spinosum is a promising source of natural antidiabetic and antioxidant compounds, particularly Undecyl 3,4,5-trihydroxybenzoate and nobiletin, which warrant further investigation.